Intermediate steps - Devos, Damien; Reynaud, Emmanuel G. (Science, 2010)
Bacteria that also have features typical of eukaryotes and archaea may reflect a possible pathway in ancient cellular evolution. Bacteria that also have features typical of eukaryotes and archaea may reflect a possible pathway in ancient cellular evolution.